CLINICAL AND NEUROLOGICAL FEATURES OF TRIGEMINAL NEUROPATHY WITH OPTIMISATION OF THERAPY IN THE ELDERLY - Machanov G.Sh.; Djurabekova A.T.; Niyozov Sh.T. (Scholar Express Journals, 2024)
Neuralgia is a secondary pathology that occurs in people over 65 years of age and arises against the background of primary diseases such as osteoporosis, osteochondrosis. According to the World Health Organization, the incidence is 2-4 people per 10 thousand people. Among all common types of the disease is trigeminal neuralgia, accompanied by severe toothache and headache, with patients unable to speak and difficulty chewing.
Keywords: elderly age; neurology; trigeminal nerve